3D shape-stable temperature-regulated macro-encapsulated phase change material: KAl(SO4)2·12H2O-C2H2O4·2H2O-CO(NH2)2 eutectic/polyurethane foam as core and carbon modified silicone resin as shell. (20th February 2022) - Chen, Weicheng; Liang, Xianghui; Han, Wanhui; Wang, Shuangfeng; Gao, Xuenong; Zhang, Zhengguo; Fang, Yutang
Highlights: The configured KAl(SO4 )2 12H2 O-C2 H2 O4 2H2 O-Urea eutectic PCM possesses excellent thermal properties. The enthalpy reduction of PCM@PUF is only 1.70% compared with PCM. CMS thin-layer with enhanced mechanical properties guarantees the thermal stability of PCM. PCM@PUF@CMS borrows from the structure of Micro-encapsulated PCM and magnifies it. Abstract: Micro-encapsulated phase change materials (PCMs) have been confirmed a high-efficiency way to store latent heat, but their poor mechanical properties, expensive and complicated synthesis block their industrial application. Herein, borrowing from this structure and magnifying it, we prepared a novel 3D shape-stable temperature-regulated macro-encapsulated PCMs. The KAl(SO4 )2 ·12H2 O-C2 H2 O4 ·2H2 O-CO(NH2 )2 (APSD-OAD-Urea) was configured as PCM to composite with light-weight porous polyurethane foam (PUF) framework, and the enthalpy reduction of PCM@PUF (core) was only 1.70%. Subsequent, carbon modified silicone resin (CMS, shell) was introduced to macro-encapsulate PCM@PUF. The results showed that with the optimized mass ratio of 75%APSD-25%OAD and extra addition of 10% Urea, the obtained PCM had a relatively high enthalpy (194.6 J/g), appropriate phase transition temperature (42.17 °C) and suppressed supercooling (0.504 °C). CMS thin-layer with 2.0 mm thickness increased resistance to deformation, impressions, scratches, and possessed a brilliant sealing effect on PCM@PUF to achieve leak-free and operation steady of PCM. PCM@PUF@CMS with low thermal conductivity from inside out displayed an outstanding thermal insulation performance. Moreover, the fluctuation of the thermodynamic property after 150 thermal cycles is relatively small. All these above enable the application of PCM@PUF@CMS in the thermal energy storage system and provide a novel strategy for the preparation of macro-encapsulated PCMs. Graphical abstract: Image, graphical abstract